68Ga-PSMA-11 and 18F-FDG PET/CT in a Case of Ductal Adenocarcinoma of the Prostate. (20th September 2022) - Qiu, Shuang; Dong, Aisheng; Zhu, Yan; Zuo, Changjing
Abstract: Prostatic ductal adenocarcinoma is an uncommon variant of prostatic carcinoma with aggressive behavior and worse prognosis. We describe 68 Ga-PSMA-11 and FDG PET/CT findings in a case of prostatic ductal adenocarcinoma with pelvic lymph node metastases. The majority of the prostate tumor and all the metastatic lesions showed no significant PSMA uptake but intense FDG uptake. The role of PSMA and FDG PET in the management of prostatic ductal adenocarcinoma needs to be investigated in a large number of patients.